Taxonomic notes on Phaneropterinae and Tettigoniinae (Orthoptera: Tettigoniidae) from the Palaearctic Region - Ünal, Mustafa (Zootaxa, 2025)
The role of female specimens in taxonomic and systematic studies, as well as the significance of accurate matching of males and females, especially among syntopic congeners, are highlighted. One hundred and twelve (112) species and subspecies of Phaneropterinae (36) and Tettigoniinae (76) are examined. The genus Nephoptera Uvarov, 1929 is reviewed at the generic level. The subgenus Erdemia Koçak et Kemal, 2009 (of Phaneroptera) is transferred to Nephoptera. A new subgenus, Exonephoptera subgen. nov. is established for the only Chinese species of this genus, Nephoptera sinica Steinmann, 1966. A key for the subgenera of Nephoptera is proposed. Unknown male of Nephoptera (s.str.) afghana Cejchan, 1969 stat. nov. is described. All known species of Nephoptera s. lat. are listed with their taxonomic histories, type information, and distributions. The following 11 new species and subspecies of Phaneropterinae (7) and Tettigoniinae (4) from Turkey are described: Isophya bozlak Ünal, sp. nov., Poecilimon allegro Ünal, sp. nov., Poecilimon luwi Ünal, sp. nov., Poecilimon helleri zeybek Ünal, ssp. nov., Poecilimon pala Ünal, sp. nov., Poecilimon bosphoricus septemlacus Ünal, ssp. nov., and Poecilimon ilgazi Ünal et Erden, sp. nov., Anadolua schwarzi autumnalis Ünal, ssp. nov., Parapholidoptera hepat Ünal, sp. nov., Parapholidoptera euxina Ünal, sp. nov. and Parapholidoptera euxina boluensis Ünal et Erden, ssp. nov. The authorship of the following species is discussed and changed as Fieber, 1878 (in Brunner von Wattenwyl 1878: 38, 44, 45, 47, 50, respectively): Poecilimon concinnus, Poecilimon obesus, Poecilimon propinquus, Poecilimon elegans, Poecilimon fussi, and Poecilimon nobilis. Lectotypes for the following 14 species of Phaneropterinae (7) and Tettigoniinae (7) are designated: Isophya schneideri Brunner von Wattenwyl, 1878, Isophya acuminata Brunner von Wattenwyl, 1878, Isophya pavelii Brunner von Wattenwyl, 1878, Poecilimon sanctipauli Brunner von Wattenwyl, 1878, Poecilimon amissus Brunner von Wattenwyl, 1878, Poecilimon anatolicus Ramme, 1933, Poecilimon bosphoricus Brunner von Wattenwyl, 1878, Gampsocleis recticauda Werner, 1901, Platycleis (Tessellana) tessellata holoptera (Ramme, 1951), Parapholidoptera signata (Brunner von Wattenwyl, 1861), Parapholidoptera castaneoviridis (Brunner von Wattenwyl, 1882), Apholidoptera pietschmanni (Ebner, 1912), Eupholidoptera annulipes (Brunner von Wattenwyl, 1882) and Eupholidoptera ledereri (Fieber, 1861). Neotypes for 2 species of Phaneropterinae, Poecilimon bidens Retowski, 1889, and Poecilimon similis Retowski, 1889, are designated. Poecilimon anatolicus Ramme, 1933 sp. rev., Poecilimon rufonitens Ingrisch et Pavicevic, 1985 sp. rev., Tettigonia turcica Ramme, 1951 sp. rev., and Anadolua burri Karabağ, 1952 sp. rev. are reverted as valid taxa. The following 10 taxa are proposed as synonyms: Phaneroptera (Erdemia) erdemi Koçak et Kemal, 2009 syn. nov. [with Nephoptera (Erdemia) hackeri (Harz, 1988)], Anadolua bergeri Şirin, Sevgili et Taylan, 2024 syn. nov. (with Anadolua burri Karabağ, 1952), Psorodonotus giresun Kaya et Çıplak, 2014 syn. nov. (with Psorodonotus soganli Ünal, 2013), Bolua balikesirensis Uluar et Çıplak, 2022 syn. nov. and Bolua bursaensis Uluar et Çıplak, 2022 syn. nov. (with Bolua turkiyae Ünal, 1999), Anterastes kizkayasiensis Çıplak et Uluar, 2023 syn. nov. (with Anterastes babadaghi Uvarov, 1939), Anterastes muratdagensis Çıplak et Uluar, 2023 syn. nov. (with Anterastes burri Karabağ, 1951), Anterastes boreoanatoliensis Çıplak et Uluar, 2023 syn. nov. [with Anterastes serbicus (Schulthess-Rechberg, 1882)], genus Aparapholidoptera Çıplak, 2021 syn. nov. (with Parapholidoptera Maran, 1953), subgenus Hamatopoecilimon Heller, 2011 syn. nov. (with Poecilimon Fischer, 1853). Some previous synonyms are confirmed. Platycleis iljinskii (Uvarov, 1917) and Platycleis pamirica (Ramme, 1930) are transferred from the nominotypical subgenus to the subgenus Squamiana Zeuner, 1941. Faunistically, the genus Nephoptera Uvarov, 1929, and Poecilimon geoktschajcus Stschelkanovtsev, 1909 are recorded from Turkey for the first time. Many species are recorded from new localities. 334 figures are provided.